Prevalence and Severity of Scabies (Sarcoptes scabiei) on Rabbits in Kuala Lumpur City - Veena Vasheene Vijaya Kumar; Mustofa Helmi Effendi; Nunuk Dyah Retno Lastuti; Nusdianto Triakoso; Maudika Pamela Fiorenza (Journal of Parasite Science (JoPS), 2022)
This study intends to know the prevalence and crusting severity of scabies (Sarcoptes scabiei) on Rabbits in Kuala Lumpur Rabbit Farm. Sarcoptes scabiei is a mite that has a predilection in the stratum corneum of the skin and caused scabies. Clinical symptoms were characterized by alopecia and crusting in the skin. This study presents a laboratory explorative research with a cross-sectional approach. Samples used rabbits in the farm that showed the clinical symptoms of scabies and the result of scraping skin in a native examination at the laboratory. Rabbits that positive scabies then performed scoring by the severity based on the region of the body and clinical symptoms. Results showed that from 140 rabbits in the population, the positive result is 13 rabbits were infected by scabies and there were 2 grades of crusting severity of scabies consisting of mild and moderate grade with separated 2 regions of the body. The low grade showed the alopecia and crusting in the face region while the medium grade in the face and foot region. The conclusion of this study is the number of prevalence scabies is 9.29% and crusting severity that low grade is 69.32% and medium grade is 30.78%.